Frater Petrus Collationes de tempore (Fourteenth Century) : Volume 2: Collations 64-150, First Sunday after Easter through Ordinary Time - Nodes, Daniel (Late Antiquity and Medieval Studies E-Books Online, Collection 2026., 2025)
The Latin sermons published for the first time are attributed to an otherwise unknown Franciscan friar referred to as Frater Petrus. This second volume of his Collationes de tempore, covering the First Sunday after Easter through Ordinary Time, comprises all the remaining entries for Sundays and major feasts in a full year's cycle. The sermons in volume two are preserved in a single fourteenth-century manuscript from Germany. Theologically competent and gracefully presented in the conventional sermon style of the period, the collection served religious communities and provided material for preaching in the vernacular for the general public. The themes as developed offer evidence of actual preaching in a typical setting from the period between the founding of the Franciscan order and the Observant reform movement. These sermons were not composed by a major light of the order, but by a rank-and-file friar who may have held the status of an intermediate-level teacher, judging by the care with which the collection was copied and indexed. Edited and translated by Daniel Nodes, the Collationes de tempore of Frater Petrus offers scholars and students a reliable new resource in an area of sermon studies still in short supply.